Nonprofit management all-in-one for dummies - Browning, Beverly A., 1948-; Farris, Sharon; Loughran, Maire; Connolly, Alyson; Singh, Shiv; Diamond, Stephanie (--For dummies., 2023)
Learn the ins-and-outs of managing, funding, and handling the accounting for a nonprofit Nonprofits are not like other businesses. They're special. It doesn't matter if you're launching a career as part of a multi-million dollar organization or a volunteer running your local little league, you'll need special know-how to navigate the accounting practices and funding needs of a not-for-profit. Nonprofit Management All-in-One For Dummies is your guide for know-how on making a nonprofit organization operate properly. This beginner-friendly reference helps replace your shelf of nonprofit how-to books with a single reference to answer your questions on how to manage a mission-focused organization, build budgets, and raise funds while staying within the confines of the laws governing nonprofits. You'll also find advice on valuable skills like marketing that benefit your organization. Learn how to run a nonprofit organization Find funding for your organization and stay tax compliant Get a grasp on nonprofit accounting principles Market your organization and fulfill your mission This 5-books-in-1 Dummies guide is excellent for volunteers who step up to run a nonprofit that's near and dear to their hearts or would-be professional non-profit managers who need advice on how to manage and grow an organization.